HISTORY, TRAUMA, DEMYSTIFICATION AND NARRATIVE IN THE NOVELS DARKNESS AND ANIMAL KINGDOM BY DAVID ALBAHARI (Heritage, 2024)
The paper explores the themes of history, trauma, demystification, and narrative present in the novels Dark and Animal Kingdom, written by the Serbian writer David Albahari. It begins with an introduction that discusses Albahari’s literary opus, with a special emphasis on its classification, narrative techniques, relation to history and other issues relevant to the topic of the paper. After that, the research methodology is introduced, along with basic information about the novels Dark and Animal Kingdom. In the central part of the paper, these novels are discussed in detail and analyzed individually and with regards to relevant parameters conditioned by the theme of the paper (history, trauma, demystification). It is performed through careful observation and analysis of the narrative text, characters and actions in both novels and provided with appropriate quotations from the novels, discussed and commented. Finally, in the concluding section of the paper, the novels are considered as a whole, with the overview of their (common) narrative characteristics and the making of final conclusive remarks.
Keywords: David Albahari, history, trauma, narration, demystification, novel, Darkness, Animal Kingdom